The role of personality and behavioural plasticity in common blackbird (Turdus merula) reproductive success : a thesis presented in partial fulfilment of the requirement for the degree of Doctor of Philosophy in Ecology at Massey University, Auckland Campus, New Zealand - Tavasoli, Mehrnaz (Massey University, 2022)
Behavioural biologists have focused on differences between species and populations in the past, while the importance of individuality in behavioural traits has been neglected for a long time. Within a population, behavioural phenotypic variation between individuals is common (Laland and Hoppitt, 2003). Recently the study of behavioural traits in individuals has attracted noticeable attention. This has resulted in behavioural ecology researchers developing a strong interest in the concept of animal personality, plasticity, and the role of individual variation in shaping behavioural traits. Additionally, behavioural ecologists have found different correlations between behavioural traits in terms of “behavioural syndromes” (Garamszegi and Herczeg, 2012). Behavioural phenotypes may cause different lifestyles, influencing life-history strategies in populations (Cote et al., 2008; Edenbrow and Croft, 2011). I investigated in depth the breeding biology and behavioural traits of a population of common blackbirds (Turdus merula; hereafter blackbirds) in New Zealand during breeding and non-breeding seasons from 2017 to 2019. In addition, I studied behavioural variation in this species. The key objective was to focus on how personality and plasticity in traits contribute to reproductive success in this species. My study used field observations and experimental approaches to investigate blackbird behavioural variation and its consequences for reproductive success. I presented breeding biology of blackbirds by investigating three key objectives: breeding biology and chronology, nest characteristics and parental provisioning in blackbirds. I found that blackbirds had a consistent number of eggs per clutch (mean= 2.9 eggs). I found a strong positive correlation between clutch size and latitude from blackbird breeding data around the world. Within breeding pairs that had more than one clutch, the number of fledged nestlings was significantly greater in the last clutches. Nests close to the road had a higher chance to be successful and fledged chicks. These results indicated evidence that predators strongly influenced the breeding success of blackbirds across the season. In addition, I found that the nest diameter increased across the breeding phases (from built to fledged chicks). In contrast, the nest thickness, internal nest depth, and external nest depth decreased. There was a positive correlation between the nest thickness/external nest depth and the number of eggs per clutch. Male and female blackbirds shared chick feeding equally. Additionally, I investigated the variation of behavioural traits of blackbirds using two approaches: observational and experimental. In the observational approach, I recorded activity, vigilance, aggressiveness and shyness behavioural traits. The experimental tests aimed to measure risk-taking within individuals, neophobia, and antipredator behaviour within paired blackbirds. Here, I focused on four objectives: 1) determine explanatory factors that influence behavioural traits (e.g., weather conditions, sexes and age, human modification), 2) estimate repeatability and consistency of all behavioural traits over different time scales within individuals, 3) examine the correlation between behavioural traits, 4) evaluate the relationship between behavioural traits and reproductive success within individuals. My results showed that activity, aggressiveness, and risk-taking behaviours increased significantly in the breeding season within individuals. Minimum temperature significantly affected the variation of behavioural traits. In addition, in the presence of a novel object, movement around the novel object and inspection time significantly increased in paired blackbirds. Inspection declined by increasing the number of trials. My results also demonstrated that the blackbird’s movement around the novel object was influenced by age and the number of chicks. Pairs that had more chicks had a greater number of movements around the novel object. Nest visits by paired blackbirds declined in the presence of the novel object and a greater number of people. Furthermore, in the presence of a predator model, blackbirds showed aggressive (attack-alarm) and non-aggressive responses (they did not alarm and attacks and fed chicks) toward the predator model, with highly aggressive and less aggressive pairs. The aggressive responses of blackbirds were affected by the age and number of nestlings in the nest. Repeatability analysis showed that the onset of egg-laying and the nest's thickness were moderately repeatable within females. Selected behavioural traits in the context of foraging were not repeatable (movement , aggressiveness, vigilant, shyness were highly flexible). However, I found that risk-taking behaviour was moderately repeatable within juvenile females and males (during breeding season) and tended to decrease in the non-breeding season. Neophobic response variables were moderately repeatable within paired blackbirds. Within pairs, antipredator responses were highly repeatable. In contrast, parental nest visits had a low repeatability estimation. Furthermore, the behavioural syndrome analysis revealed a positive correlation between activity and shyness. I also discovered risk-taker blackbirds were more vigilant. Regarding the consequences of behavioural traits on blackbird breeding, I found that shyer blackbirds had a greater number of fledged nestlings per season. In addition, blackbirds who were risk-takers (shorter FIDs, flight initiation distance) produced more eggs per season. Antipredator responses and neophobia in blackbirds were also influenced by breeding investments of blackbirds. Movement round the novel object (neophobic response) and aggressive response toward a predator increased in pairs with a greater number of chicks. In the post-stress situation (predator presentation), pairs with more chicks in their nests returned to their nests sooner (shorter latency) and had a greater number of post-stress nest visits. Additionally, I investigated the response of male blackbirds to different conspecific songs by two playback experiments. In the first experiment, I investigated if blackbirds display different responses to playback songs from males of varying levels of aggressiveness. I also investigated the effect of anthropogenic disturbance, parental care and breeding success on the response of blackbirds to the playback. In the second playback experiment, I examined whether male blackbirds discriminated songs (a long-range signal) from neighbouring and stranger conspecifics. Results from my playback experiment revealed that there were no differences in the response of male blackbirds to the songs from aggressive and non-aggressive blackbirds. Interestingly, blackbirds that had their territories close to the road showed stronger responses toward the playback songs. In addition, there was a positive correlation between the response of male blackbirds and the number of nest visits during the chicks rearing. My results from the second playback experiment showed that a male blackbird responded equally to the dawn songs from his neighbours and strangers, while his response to the songs from far strangers (blackbird’s songs recorded in Europe) was weaker than New Zealand blackbird songs. However, I also found that males respond to stranger blackbirds' daytime songs stronger than those from the neighbour, which confirmed the “Dear Enemy” theory in blackbirds. My research is significant in that it is one of the first studies of breeding and behavioural traits of blackbirds in an urban population of New Zealand. It provides important highlights about intra-individual variation in behavioural traits, and its fitness consequences on the breeding success of blackbirds.
Keywords: European blackbird; Behavior; Reproduction; New Zealand; 310901 Animal behaviour